The Impact of Transformational Leadership, Transactional Leadership, and Knowledge Management on Innovation Mediated by Human Capital in The Pharmaceutical Industry in Indonesia - Sitorus, Mompo Uli; Hendratmoko, Hendratmoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The objective of this research is to find out how transformational leadership, transactional leadership, and knowledge management impact innovation mediated by human capital in the Pharmaceutical Industry in Indonesia. Quantitative analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) utilizing SmartPLS 4 software. An online questionnaire was carried out to obtain the data and the responses from 203 respondents resulted in 186 usable from 30 pharmaceutical industries across Indonesia. The findings point out that the direct effects of transformational leadership (TL), transactional leadership (TC), knowledge management (KN), and human capital (HC) relate positively and significantly to innovation (IN). The findings also confirmed that human capital mediates partially (complementary) the effect of transformational leadership on innovation, transactional leadership on innovation, and knowledge management on innovation. Based on this study to optimize innovation performance, it was suggested that pharmaceutical companies in Indonesia need to maintain the performance of any indicators that are already running well, and also need to put more effort into knowledge exchange among employees as well as the level of using new methods to improve efficiency and effectiveness of existing processes.